COMPARISON OF SEVERAL RED EDGE BAND SENTINEL SATELLITE IMAGERY FOR MANGROVE MAPPING IN LEMBAR BAY LOMBOK INDONESIA - Sukuryadi Sukuryadi; Harry Irawan Johari; Nurin Rochayati; Mas'ad Mas'ad; Alfian Pujian Hadi (GEOGRAPHY : Jurnal Kajian, Penelitian dan Pengembangan Pendidikan, 2021)
The use of the vegetation index algorithm in determining density is a challenge for researchers to find out the ability of an algorithm to accurately present vegetation information. Each vegetation index produces different accuracy values for the value of the density of mangroves depending on the combination of bands used. This study aimed  to evaluate those red edge band sentinel satellite imagery 2B for mangrove mapping using the algorithm of modified SR and NDVI. The research method used is the direct or indirect survey method. The algorithm analysis of the vegetation index used in this study is NDVIred edge, NDVIred and red edge, MSRred edge, MSRred  and red edge. Correlation analysis, determinant, and Root Mean Square Error (RMSE) were used to test the accuracy of the analysis results for each of the vegetation index algorithms. Based on the comparison results, the NDVIred and red edge algorithm are the most reliable because they have the lowest RMSE value (0.05) with a high correlation and determinant coefficient values between the vegetation index values with their respective field density values 82 % and 0.90. Thus, the extraction results of the NDVIred and red edge algorithm are the closest to the actual conditions in the field.